Türk sinemasında kadın yönetmenler - Çetin, Vildan (My University, 2001)
TEZ ÖZETİ TÜRK SİNEMASINDA KADIN YÖNETMENLER nemasında Kadın Yönetmenler yüksek lisans çalışmamızın ilk bölümünde ilk olarak Türk Sinema tarihini ve gelişim sürecini inceledik. Bu bölümde gördük ki; Türk Sinemasında melodram ağırlıklı bir Yeşilçam geleneğinden, arabeske, seks filmleri furyasından, kadın filmlerine ve siyasal içerikli filmlere kadar geniş bir yelpazede ürünlerverilmiş.İkinci Bölüm, Kadın Hareketleri ve Feminizm konusu ile ilgiliydi. Dünyada yaşanan gelişmeler ve bunun Türkiye'deki yansımaları inceledik. kazanmış.Üçüncü Bölüm, Türk Sinemasında Kadının Sunumu konusu ile ilgiliydi. Kadın yönetmenleri daha iyi anlamak için sinemamızda kadına nasıl bakıldığını bilmek gerekiyordu çünkü. Önceleri kesin çizgilerle ayrılan kadın anlayışının (iyi kadın/ kötü kadın), yavaş yavaş yerini olumlu ya da olumsuz yanlarıyla gerçek hayattaki kadına bıraktığını gördük. Dördüncü Bölüm, Türk Sinemasında Kadın Yönetmenler ile ilgili yaptığımız araştırmaların yer aldığı bir bölümdü. İlk dönemler sayıları parmakla gösterilecek kadar az olan kadın yönetmenlerimizin, 80 sonrası kadın hareketlerinde görülen ivme artışı ile çoğaldığını ve başarılı yapıtlar ortaya çıkardıklarını gördük. Sonuç Bölümü, yazdıklarımızın tümünden ortaya çıkan, sinemada kadın yönetmenler vardır ve olacaktır; çünkü ataerkil sistemin özelliklerine dayanmayan ve insancıl bir bakış açısı taşıyan farklı lezzetlerde filmler izlemek istiyorsak kadın yönetmenlere kesinlikle ihtiyacımız vardır sonucunun yer aldığı bölümdü. GRADUATE THESIS WOMEN DIRECTORS IN TURKISH FILM INDUSTRY

First section of this graduate thesis submitted under the title Women Directors in Turkish Film Industry deals with the historical background of Turkish Film Industry and its recent development so far in our contemporary period. Surprisingly enough, we have encountered substantial wide spectrum of the theme ranging from melodramatic films focused on mainly conventional Yeşilçam comprehension to so called arabesque films, frequently rushing to pornographic films at last resort, theme on women issues here and there, and last but not least political films as expected. Section two mainly handles the infrequent theme of Women Movements and Feminism. The reflections on Turkish film of worldwide developments in this area were scrutinized. Throughout this section, we have observed that the women movement in Turkey has accomplished great deal of achievement in the course marked by 1980's. Section three deals with the comprehension in the presentation of the women within Turkish film. This is because the way that the women were dealt should be known, in order to comprehend better the role of the women director. Eventually we have seen that women were appearing more likely as they are in real life with their favourable and unfavourable attributes rather than comprehension toward the women classified with a distinct features (good woman/ bad woman). Section four covers our outlook upon investigation conducted so far on Women Directors in Turkish. We have perceived that, the number of the women directors, once so few as to be counted by the finger so to speak, were increasing after 80's along with the overall women movement and have accomplished great deal achievements. The last section, finally, provide us nothing but the proof to all what we have concluded within this context, to put it another way, the existence of the women in the film industry now and in the future; this is because, we need them, we need the women directors should we ever be longing for the performances that provides us different point of view, inspired from humanistic values, apart from those which are mainly based on the privileges of the patriarchal understanding.
Keywords: Kadınlar-Türkiye; Sinema_Yönetmenlik